Development of Gluten-Free Breads Using Andean Native Grains Quinoa, Kañiwa, Kiwicha and Tarwi - Ritva Repo-Carrasco-Valencia; Julio Vidaurre-Ruiz; Genny Isabel Luna-Mercado (Proceedings, 2020)
The aim of this study was to develop gluten-free breads using the flours of Andean native grains. The following native grains were used: quinoa (Chenopodium quinoa) Pasankalla variety, kiwicha (Amaranthus caudatus) Centenario variety, kañiwa (Cheopodium pallidicaule) Illpa Inia variety and tarwi (Lupinus mutabilis) Blanco de Yunguyo variety. The formulations of the breads with Andean grains flours were optimized using the Mixture Design and the Central Composite Rotational Design, analyzing the dough’s textural properties (firmness, consistency, cohesiveness and viscosity index), specific volume and crumb texture. Potato starch and xanthan gum were used in the preparation of the breads. The optimized formulations of the gluten-free breads with Andean grain flours were composed of quinoa (46.3%), kiwicha (40.6%), kañiwa (100%) and tarwi (12%) flours. The gluten-free breads developed showed acceptable specific volume and low crumb firmness and could help to improve the nutrition of celiac patients.